2019
DOI: 10.3390/su11154095
|View full text |Cite
|
Sign up to set email alerts
|

Living Lab as an Ecosystem for Development, Demonstration and Assessment of Autonomous Mobility Solutions

Abstract: Autonomous vehicles (AV) have the potential to disrupt the entire transport industry. AV may bring many opportunities as for example reduction of road accidents, less congestion on the roads, and a lower number of vehicles that are better utilized. Full AV also brings new social element as they enable mobility for all. In addition, the use of digital technologies in combination with AV introduces new business models in transportation, where the lines between car ownership, rental, and lease modes are more and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…There are two ways to measure intention to use: intention to use for some use-cases or for a shared or owned vehicle, or general intention to use. When participants are asked to evaluate different use cases, they tend to approve of all of them Ledger et al, 2018;Leicht et al, 2018;Nielsen & Haustein, 2018;Nishihori et al, 2017;Nordhoff et al, 2019;Pucihar et al, 2019;Rahman et al, 2019;Regan et al, 2017;Rehrl & Zankl, 2018), except driving children without an adult present (Kaur & Rampersad, 2018;Ledger et al, 2018;Lee & Mirman, 2018;Lustgarten & Le Vine, 2018;Regan et al, 2017). This result is similar in studies that provide no information, only a brief definition or that include AV experience.…”
Section: Iii32 Operationalization and Definition Of Acceptability And Intention To Usementioning
confidence: 65%
See 2 more Smart Citations
“…There are two ways to measure intention to use: intention to use for some use-cases or for a shared or owned vehicle, or general intention to use. When participants are asked to evaluate different use cases, they tend to approve of all of them Ledger et al, 2018;Leicht et al, 2018;Nielsen & Haustein, 2018;Nishihori et al, 2017;Nordhoff et al, 2019;Pucihar et al, 2019;Rahman et al, 2019;Regan et al, 2017;Rehrl & Zankl, 2018), except driving children without an adult present (Kaur & Rampersad, 2018;Ledger et al, 2018;Lee & Mirman, 2018;Lustgarten & Le Vine, 2018;Regan et al, 2017). This result is similar in studies that provide no information, only a brief definition or that include AV experience.…”
Section: Iii32 Operationalization and Definition Of Acceptability And Intention To Usementioning
confidence: 65%
“…The results also showed that trust may vary depending on the reliability. Trust was higher when the AV was reliable than when it performed poorly (Pucihar et al, 2019;Rovira et al, 2019). Trust was thus negatively affected by perceived risks (Choi & Ji, 2015;Rovira et al, 2019).…”
Section: Iii34 Perceptionsmentioning
confidence: 98%
See 1 more Smart Citation
“…According to the literature, numerous studies aim to identify innovative solutions for the improvement of traffic mobility from different points of view. Reference is made, for example, to the study on on-demand mobility services (Faisal et al 2019; Freudendal-Pedersen, Kesselring, and Servou 2019; Marletto 2019; Pucihar et al 2019), to the development of systems that can integrate connected vehicle data and traffic sensor information (Yang et al 2019), and to the use of high-definition smart cameras with wireless communication (Ho et al 2019) to simultaneously address the need to improve the safety and mobility of urban arteries. These systems aim to reduce the potential accident rate, monitor traffic, and calculate the length of the queues at intersections as a function of time to improve arterial progression.…”
Section: Results From Camentioning
confidence: 99%
“…One example that discusses residents' participation in a tourism context will be cited here. Pucihar et al (2019) stress tourists as a source of innovation and a target group-oriented approach: Through living labs, "tourist service providers will obtain insight into what tourists actually want and will have an opportunity to improve and develop new services targeted to different customer segments" [152]. By expanding this user-centric approach, the ideal LL is probably a user-driven LL, which is fully based on self-governance.…”
Section: Living Labs In Residents' Participationmentioning
confidence: 99%